2018
DOI: 10.1103/physrevlett.121.161301
|View full text |Cite
|
Sign up to set email alerts
|

Optical Ring Cavity Search for Axion Dark Matter

Abstract: We propose a novel experiment to search for axion dark matter which differentiates the phase velocities of the left and right-handed polarized photons. Our optical cavity measures the difference of the resonant frequencies between two circular-polarizations of the laser beam. The design of our cavity adopts double-pass configuration to realize a null experiment and give a high common mode rejection of environmental disturbances. We estimate the potential sensitivity to the axion-photon coupling constant gaγ fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 64 publications
2
86
0
Order By: Relevance
“…We estimated the potential sensitivity of detectors to the axion-photon coupling in a broad mass range 10 −16 eV m 10 −9 eV with the experimental parameters of existing gravitational wave detector projects, such as DECIGO, CE and aLIGO. As a result, we found that their sensitivities can reach beyond the current limit of CAST [5] with a wide axion mass range and can be competitive with other experimental proposals which were recently suggested [25][26][27]. Remarkably, our new scheme for axion-like dark matter search can be performed with a minor modification of the gravitational wave detector and coexist with its observation run for gravitational waves.…”
Section: Sensitivity To the Axion-photon Couplingmentioning
confidence: 61%
See 1 more Smart Citation
“…We estimated the potential sensitivity of detectors to the axion-photon coupling in a broad mass range 10 −16 eV m 10 −9 eV with the experimental parameters of existing gravitational wave detector projects, such as DECIGO, CE and aLIGO. As a result, we found that their sensitivities can reach beyond the current limit of CAST [5] with a wide axion mass range and can be competitive with other experimental proposals which were recently suggested [25][26][27]. Remarkably, our new scheme for axion-like dark matter search can be performed with a minor modification of the gravitational wave detector and coexist with its observation run for gravitational waves.…”
Section: Sensitivity To the Axion-photon Couplingmentioning
confidence: 61%
“…The gray and green band express the current limit provided by CAST [5] and the cosmic ray observations of SN1987A [14]. The red dashed line is a sensitivity curve of one proposed experiment using optical ring cavity with optimistic parameters [26].…”
Section: Sensitivity To the Axion-photon Couplingmentioning
confidence: 99%
“…We have proposed the Fourier-space analysis using the light from various astrophysical sources. We concentrated on the light from astrophysical sources, but a similar analysis may be performed in the proposed ALP search using optical cavity [58,59] or gravitational wave detector [60]. The discovery reach depends on the performance of the detector (i.e., the time required to observe the polarization of the light from a single sky patch and the size of the noise in the observation) as well as the period available for the observation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, several novel methods have been proposed to measure this modulated phase velocity difference using carefully designed optical cavities [2,4,3,5]. The phase velocity difference gives resonant frequency difference between two circular polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…The proposal in Ref. [4] instead uses a bow-tie ring cavity to avoid losses from wave plates, and uses a double-pass configuration to eliminate displacement noises.…”
Section: Introductionmentioning
confidence: 99%